2007
DOI: 10.1042/bj20070404
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin inhibits regulated secretion of endothelial cell von Willebrand factor in response to diverse secretagogues

Abstract: Regulated secretion of EC (endothelial cell) vWF (von Willebrand factor) is part of the haemostatic response. It occurs in response to secretagogues that raise intracellular calcium or cAMP. Statins are cholesterol-lowering drugs used for the treatment of cardiovascular disease. We studied the effect of fluvastatin on regulated secretion of vWF from HUVEC (human umbilical-vein ECs). Secretion in response to thrombin, a protease-activated receptor-1 agonist peptide, histamine, forskolin and adrenaline (epinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…However, fluvastatin's influence on eNOS activity and expression was already described in endothelial cells [27][28][29]. Harris et al [27] reported acute effect of statin on eNOS phosphorylation and activity, while Fish et al [28] reported the increased expression of eNOS by fluvastatin. Meda et al [29] included importance of statin-induced tetrahydrobiopterin (BH4) in their report.…”
Section: Discussionmentioning
confidence: 96%
“…However, fluvastatin's influence on eNOS activity and expression was already described in endothelial cells [27][28][29]. Harris et al [27] reported acute effect of statin on eNOS phosphorylation and activity, while Fish et al [28] reported the increased expression of eNOS by fluvastatin. Meda et al [29] included importance of statin-induced tetrahydrobiopterin (BH4) in their report.…”
Section: Discussionmentioning
confidence: 96%
“…Another explanation may be that at the time of inclusion, all patients with CVD used statins that are known to decrease VWF levels, probably by influencing VWF secretion. 23,24 Therefore, use of statins may have attenuated the association between genetic variation and VWF:Ag levels. Thus far, SNP rs1063857 was associated with an increase in VWF:Ag levels and with the risk for disease in 2 independent studies, which suggests that VWF may be a causal factor in the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Statins, however, improve several EC functions, 19 including the secretion of VWF from EC stimulated with thrombin. 27 Here, we report on the effect of atorvastatin on VWF release and platelet adhesion to HUVEC on exposure to cocaine and plasma from chronic cocaine consumers.…”
Section: Resultsmentioning
confidence: 99%